Efficacy of fixed-dose combination artesunate-amodiaquine versus artemether-lumefantrine for uncomplicated childhood Plasmodium falciparum malaria in Democratic Republic of Congo: a randomized non-inferiority trial. - Espié, E; Lima, A; Atua, B; Dhorda, M; Flévaud, L; Sompwe, E; Palma Urrutia, P; Guerin, P (BioMed Central, 2012)
Background: In 2005, the Democratic Republic of Congo (DRC) adopted artesunate and amodiaquine (ASAQ) as first-line anti-malarial treatment. In order to compare the efficacy of the fixed-dose formulation ASAQ versus artemether-lumefantrine (AL), a randomized, non-inferiority open-label trial was conducted in Katanga. Methods: Children aged six and 59 months with uncomplicated Plasmodium falciparum malaria were enrolled and randomly allocated into one of the two regimens. The risk of recurrent parasitaemia by day 42, both unadjusted and adjusted by PCR genotyping to distinguish recrudescence from new infection, was analysed. Results: Between April 2008 and March 2009, 301 children were included: 156 with ASAQ and 145 with AL. No early treatment failures were reported. Among the 256 patients followed-up at day 42, 32 patients developed late clinical or parasitological failure (9.9% (13/131) in the ASAQ group and 15.2% (19/125) in the AL group). After PCR correction, cure rates were 98.3% (95%CI, 94.1-99.8) in the ASAQ group and 99.1% (95%CI, 94.9-99.9) in the AL group (difference −0.7%, one sided 95% CI −3.1). Kaplan-Meier PCR-adjusted cure rates were similar. Both treatment regimens were generally well tolerated. Conclusion: Both ASAQ and AL are highly effective and currently adequate as the first-line treatment of uncomplicated falciparum malaria in this area of Katanga, DRC. However, in a very large country, such as DRC, and because of possible emergence of resistance from other endemic regions, surveillance of efficacy of artemisinin-based combination treatments, including other evaluations of the resistance of ASAQ, need to be done in other provinces. Trial registration: The protocol was registered with the clinicaltrials.gov, open clinical trial registry under the identifier number NCT01567423.